A molecular dynamics study of the effects of crystalline structure transition on the thermal conductivity of pentaerythritol as a solid-solid phase change material. (October 2019) - Feng, Biao; Tu, Jing; Sun, Ju-Wei; Fan, Li-Wu; Zeng, Yi
Highlights: The effects of crystalline structure on the thermal conductivity of PE are studied. Microscale mechanisms due to structure transition are explored by MD simulations. The thermal conductivity of PE is reduced by a half after the α-to-γ phase change. Strong intermolecular HBs break off and form weaker HBs during the phase change. The distinguished heat transfer capability of HBs is calculated and demonstrated. Abstract: A typical polyol that experiences solid-solid phase transitions, pentaerythritol (PE) has been proposed as a promising phase change material candidate for latent heat storage pertinent to the temperature range for industrial waste heat recovery. Upon increasing the temperature to over the solid-solid phase transition point (∼459 K), body-centered tetragonal crystalline structure of PE (α phase) is transformed into orientationally disordered face-centered cubic crystalline structure (γ phase). The thermal conductivity of PE at both α and γ phases is of great practical interest. In this work, the in situ X-ray diffraction and Fourier transformer infrared spectroscopy were used to characterize the crystalline structure transition of PE, in combination with the differential scanning calorimetry results. Molecular dynamics simulations were performed to elucidate the relationship between the thermal conductivity variation of PE and its crystalline structures at the atomic level. It was found that after the α-to-γ phase transition, the rearrangement and rotation of the OH···O bonds lead to indeterminate positions of the O and H atoms in the γ phase. The destruction and weakening of the hydrogen bonds can be the major change in the crystalline structures, leading to the reduction of the thermal conductivity of PE by a half after the α-to-γ phase transition.